Beta Thalassemia 2020
DOI: 10.5772/intechopen.92970
|View full text |Cite
|
Sign up to set email alerts
|

Nutraceutical Benefits of Green Tea in Beta-Thalassemia with Iron Overload

Abstract: Secondary iron overload in patients with β-thalassemia is caused by multiple blood transfusions and increased iron absorption. Most of them die from cardiac arrest and infections while others from oxidative tissue damage and organ dysfunction. Under high saturation of transferrin with iron, redox-active iron such as nontransferrin-bound iron, labile plasma iron, and cellular labile iron pool is prone to the production of reactive oxygen species, oxidized biomolecules, oxidative tissue damages, and complication… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 117 publications
1
0
0
Order By: Relevance
“…Remarkably, it also restored the decreased hepatic Hamp1 mRNA expression levels in ferrocene−fed BKO mice (Upanan et al, 2015). Consistently, we have revealed that GTE effectively chelated the iron in the liver and decreased the ROS in ferrocene−fed BKO mice (Srichairatanakool et al, 2006;Saewong et al, 2010;Koonyosying et al, 2020a). Lastly, we have confirmed that levels of TBARS are used as simple biomarkers for the assessment of oxidative status in β−thalassemia patients (Meral et al, 2000;Ondei Lde et al, 2013) in the plasma, liver, spleen and kidneys of iron dextran−loaded BKO mice were dramatically decreased after treatments of GTE, DFP and a combination of the two when compared to mice that had not received treatment (DI group).…”
Section: Discussionsupporting
confidence: 79%
“…Remarkably, it also restored the decreased hepatic Hamp1 mRNA expression levels in ferrocene−fed BKO mice (Upanan et al, 2015). Consistently, we have revealed that GTE effectively chelated the iron in the liver and decreased the ROS in ferrocene−fed BKO mice (Srichairatanakool et al, 2006;Saewong et al, 2010;Koonyosying et al, 2020a). Lastly, we have confirmed that levels of TBARS are used as simple biomarkers for the assessment of oxidative status in β−thalassemia patients (Meral et al, 2000;Ondei Lde et al, 2013) in the plasma, liver, spleen and kidneys of iron dextran−loaded BKO mice were dramatically decreased after treatments of GTE, DFP and a combination of the two when compared to mice that had not received treatment (DI group).…”
Section: Discussionsupporting
confidence: 79%